Environment-friendly coating composition for building interiors

By mixing water-based acrylic emulsion and water-based polyurethane emulsion in a specific ratio, as well as surface-treated titanium dioxide and coated iron oxide red, the deficiencies of traditional coatings in terms of water resistance, weather resistance, flexibility and wear resistance are solved, achieving Significant improvement in coating performance and extension of service life.

CN119350936AInactive Publication Date: 2025-01-24SHAANXI JIAYUAN CONSTR TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411938380.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional architectural interior coatings have insufficient performance in water resistance, weather resistance, flexibility and wear resistance, resulting in damage, peeling, cracking and wear of the paint film, affecting the decorative effect and service life.

Method used

The water -based acrylic lotion and water -based polyurethane lotion are mixed with a specific proportional film, combined with the surface treatment of titanium pink and the oxygen oxide red treated with the surface, and the kaolin and surface modified calcium carbonate were combined with the burnt. Sodium salt decentrals and hydroxye ethyl cellulose are used as decentrals and thickeners.

Benefits of technology

It significantly improves the overall performance of the coating, enhances the water resistance, weather, flexibility and abrasion resistance of the paint film, extend the service life, reduce the maintenance cost, and ensure the long -term brightness and decorative durability of the color.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of environment-friendly building coatings, in particular to an environment-friendly coating composition for building interiors, which is prepared from the following basic components in parts by weight: 20 to 30 parts of film forming matter, 10 to 20 parts of pigment, 30 to 40 parts of filler, 2 to 5 parts of dispersing agent, 3 to 6 parts of thickening agent and 1 to 3 parts of pH regulator. The building interior environment-friendly coating composition has the remarkable advantages that the water-based acrylic emulsion and the water-based polyurethane emulsion are mixed according to a specific proportion to form a film, the water-based acrylic emulsion is resistant to water and weather and stable in dispersion, the water-based polyurethane emulsion is excellent in flexibility and abrasion resistance, the overall performance of the coating is improved through the synergistic effect of the water-based acrylic emulsion and the water-based polyurethane emulsion, and titanium dioxide subjected to surface treatment is high in dispersity and covering power; according to the present invention, the coating material composition has characteristics of good adhesion with the film forming material, cost reducing, coating performance improving, and coating material decoration durability improving, the iron oxide red subjected to the film coating treatment can maintain the bright color for a long time in the complex environment, such that the coating material composition has the excellent performance in the building interior decoration field so as to effectively solve the various problems of the existing coating material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of environmentally friendly building coatings, in particular to an environmentally friendly coating composition for building interiors. Background Art

[0002] In the field of building interiors, the performance of coatings is crucial. Traditional coating compositions have many shortcomings in practical applications.

[0003] Traditional film-forming materials often cannot provide good water resistance, weather resistance, flexibility and wear resistance. For example, the film-forming materials of some coatings may not perform well in terms of water resistance, which may cause the coating to be easily damaged and peeled off when exposed to water or humid environment for a long time, greatly shortening the service life of the coating and increasing maintenance costs. At the same time, if the flexibility and wear resistance are insufficient, the coating will easily crack and wear when subjected to slight external force or daily friction, affecting the decorative effect.

[0004] As for pigments, titanium dioxide that has not been specially treated has poor dispersion in paint and is prone to agglomeration, which means that in order to achieve the required hiding power, the amount of titanium dioxide used must be increased, thereby increasing costs. In addition, titanium dioxide has weak bonding with film-forming substances, which can easily lead to poor scrub and wear resistance of the coating, and it is difficult to ensure color uniformity. In complex building interior environments, red iron oxide has insufficient acid and alkali resistance and chemical stability, which makes its color easily change and unable to maintain its brightness for a long time, reducing the decorative durability of the paint.

[0005] In addition, fillers in traditional coatings may have problems with hardness, wear resistance, filling and leveling properties that cannot be balanced. For example, when improving hardness and filling properties, leveling properties are often sacrificed. If the performance of additives such as dispersants and thickeners is poor, it will also affect the storage stability, construction performance and final coating quality of the coating. Therefore, there is an urgent need for an environmentally friendly architectural interior coating composition with better performance to overcome these defects. Summary of the invention

[0006] In view of the above-mentioned shortcomings of the prior art, the present invention provides an environmentally friendly coating composition for building interiors. The environmentally friendly coating composition for building interiors of the present invention has significant advantages. Aqueous acrylic emulsion and aqueous polyurethane emulsion are mixed in a specific proportion to form a film. The former is water-resistant and weather-resistant and has stable dispersion, while the latter has excellent flexibility and wear resistance. The synergistic effect of the two improves the overall performance of the coating. The surface-treated titanium dioxide has strong dispersibility and hiding power, and good bonding with film-forming substances, which can reduce costs and improve coating performance. The coated red iron oxide can maintain bright colors for a long time in complex environments and enhance the durability of coating decoration. These characteristics enable the coating composition to perform excellently in the field of building interiors and effectively solve various problems existing in existing coatings.

[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions: An environmentally friendly coating composition for building interiors, the composition comprising the following basic components in parts by weight: 20-30 parts of a film-forming substance, 10-20 parts of a pigment, 30-40 parts of a filler, 2-5 parts of a dispersant, 3-6 parts of a thickener, and 1-3 parts of a pH regulator; The film-forming substance is formed by mixing an aqueous acrylic emulsion and an aqueous polyurethane emulsion in a ratio of 2:1. The glass transition temperature of the aqueous acrylic emulsion is 10-20°C, the average particle size is 0.1-0.2 μm, and the solid content is not less than 40%. The NCO content of the aqueous polyurethane emulsion is 3-5%, and the number average molecular weight is between 5000-10000. The pigment is titanium dioxide and red iron oxide. The titanium dioxide is rutile, has a particle size of 0.2-0.3 μm, and a content of 5-10 parts. The content of red iron oxide is 5-10 parts, and its particle size is 0.1-0.2 μm. The filler is a mixture of kaolin and heavy calcium carbonate, the particle size of kaolin is 1-5 μm, the content is 15-20 parts, the particle size of heavy calcium carbonate is 5-10 μm, and the content is 15-20 parts; The dispersant is a polycarboxylate sodium salt dispersant, and its molecular weight is between 5000-8000; The thickener is hydroxyethyl cellulose, and its degree of substitution is 1.5-2.0; The pH regulator is ammonia water with a concentration of 25%-28%.

[0008] Furthermore, the aqueous acrylic emulsion is prepared by free radical polymerization, in which the monomers include methyl methacrylate, butyl acrylate and hydroxyethyl acrylate in a molar ratio of 3:2:1, the initiator is ammonium persulfate in an amount of 0.5-1% of the total weight of the monomers, the reaction temperature is controlled at 70-80°C, and the reaction time is 4-6 hours; During the polymerization process, a molecular weight regulator, dodecyl mercaptan, is added in an amount of 0.2-0.3% of the total weight of the monomers. In the reaction system, the amount of water is 1.5-2 times the total weight of the monomers. The resulting aqueous acrylic emulsion has good water resistance and weather resistance, and has good dispersion stability in water, with no precipitation or stratification after being placed for 30 days.

[0009] Furthermore, the aqueous polyurethane emulsion is synthesized by a prepolymer method, and the specific steps are: Step 1, using polytetramethylene ether glycol and isophorone diisocyanate as raw materials, reacting at 80-90° C. for 2-3 hours to obtain a prepolymer, wherein the molecular weight of the polytetramethylene ether glycol is 1000-2000, and the molar ratio of isophorone diisocyanate to the polytetramethylene ether glycol is 2:1; Step 2, the prepolymer is subjected to a chain extension reaction with dimethylolpropionic acid and ethylenediamine at 50-60° C., wherein the amount of dimethylolpropionic acid is 5-10% by weight of the prepolymer, and the amount of ethylenediamine is 3-5% by weight of the prepolymer; Step 3: After the reaction is completed, triethylamine is added for neutralization with a neutralization degree of 80-90%, and then water is added for emulsification to obtain an aqueous polyurethane emulsion. The aqueous polyurethane emulsion has excellent flexibility and wear resistance, a tensile strength of 20-30 MPa, and an elongation at break of 300-400%.

[0010] Furthermore, the titanium dioxide is surface treated before use, the surface treatment agent is a mixture of a silane coupling agent and an aluminate coupling agent, the silane coupling agent is γ-aminopropyl triethoxysilane, the aluminate coupling agent is isopropyl tri(isostearoyl) titanate, the mass ratio of the two is 1:1, and the amount of the surface treatment agent is 2-3% of the weight of the titanium dioxide; The treatment process is as follows: drying the titanium dioxide at 100-120°C for 2-3 hours, adding a coupling agent, and mixing for 30-60 minutes under high-speed stirring at a stirring speed of 1000-1500rpm. The titanium dioxide after surface treatment has better dispersibility and hiding power in the coating composition, and has stronger bonding with the film-forming substance.

[0011] Furthermore, the red iron oxide is coated, and the coating material is an organic silicone resin, and the amount thereof is 5-10% of the weight of the red iron oxide; Specific processing steps: Step 1: Disperse red iron oxide in an organic solvent, wherein the organic solvent is toluene, and the concentration of red iron oxide is 20-30%; Step 2: Add silicone resin, stir and react at 60-70°C for 2-3 hours at a stirring speed of 800-1000 rpm; Step 3: After the reaction is completed, filter and dry to obtain coated red iron oxide. The coated red iron oxide has better acid and alkali resistance and chemical stability, and can maintain the color brightness for a long time in the coating.

[0012] Furthermore, the kaolin is calcined, wherein the calcination temperature is 800-900°C, the calcination time is 2-3 hours, the whiteness of the calcined kaolin is 90-95%, and the Mohs hardness is 2-3. In the coating composition, the calcined kaolin can improve the hardness and wear resistance of the coating without affecting the leveling of the coating. The crystal structure of the kaolin is more regular after calcination, and its flaky structure is more obvious, which is conducive to forming a good filling structure in the coating and reducing the shrinkage rate of the coating.

[0013] Furthermore, the heavy calcium carbonate is surface-modified, and the modifier is stearic acid, and the amount used is 1-2% of the weight of the heavy calcium carbonate; The modification process is as follows: drying the heavy calcium carbonate at 100-110°C for 1-2 hours, adding stearic acid, and mixing in a high-speed mixer for 20-30 minutes at a mixing speed of 1200-1500rpm. The dispersibility of the surface-modified heavy calcium carbonate in the coating is significantly improved, and the compatibility with the film-forming material is better, which can effectively reduce the oil absorption value of the coating, improve the filling performance of the coating, and reduce the precipitation of the coating during storage.

[0014] Furthermore, the specific steps of the synthesis method of the polycarboxylate sodium salt dispersant are: Step 1: using acrylic acid, maleic anhydride and methyl methacrylate as monomers in a molar ratio of 2:1:1; Step 2: The initiator is sodium persulfate, and the amount used is 0.3-0.5% of the total weight of the monomer; Step 3: Add chain transfer agent mercaptoethanol to the reaction system in an amount of 0.1-0.2% of the total weight of the monomers. The reaction is carried out in an aqueous solution. The amount of water is 2-3 times the total weight of the monomers. The reaction temperature is 80-90°C and the reaction time is 3-4 hours. The synthesized polycarboxylic acid sodium salt dispersant has high efficiency in dispersing performance and good dispersion stability for pigments and fillers. It can keep the coating composition in a uniform dispersion state during long-term storage and prevent agglomeration of pigments and fillers.

[0015] Furthermore, the preparation process of the hydroxyethyl cellulose is as follows: using refined cotton as a raw material, soaking it in an alkali solution for 1-2 hours, the alkali solution concentration is 18-20%, adding ethylene oxide, the mass ratio of ethylene oxide to refined cotton is 2:1, reacting under the conditions of a pressure of 0.2-0.3MPa and a temperature of 50-60°C, the reaction time is 4-5 hours, after the reaction is completed, neutralizing, washing, and drying to obtain hydroxyethyl cellulose, the obtained hydroxyethyl cellulose in the coating composition can effectively adjust the rheological properties of the coating, so that the coating has good construction performance, can form a uniform and smooth coating film during the painting process, and will not have a sagging phenomenon.

[0016] Compared with the known prior art, the technical solution provided by the present invention has the following beneficial effects: 1. The water-based acrylic emulsion of the present invention is prepared by a specific monomer ratio and polymerization conditions, has good water resistance and weather resistance, is stably dispersed in water, has no precipitation and stratification after long-term storage, effectively prolongs the service life of the coating and reduces maintenance costs. At the same time, the water-based polyurethane emulsion is synthesized by a prepolymer method, has excellent flexibility and wear resistance, a tensile strength of 20-30MPa, and an elongation at break of 300-400%. It is mixed with the water-based acrylic emulsion in a ratio of 2:1 to form a film, so that the paint film is dense and uniform, and has strong adhesion. The two work together to improve the overall performance of the coating.

[0017] 2. The dispersibility and hiding power of the titanium dioxide after surface treatment in the present invention are enhanced, and it is evenly distributed in the paint. A good hiding effect can be achieved by reducing the amount used, thereby reducing costs. It also has a strong bonding force with the film-forming substance, thereby improving the scrub resistance and wear resistance of the coating and maintaining color uniformity. At the same time, the red iron oxide after coating treatment has good acid and alkali resistance and chemical stability, and can maintain bright colors for a long time in the complex environment of building interiors, thereby improving the durability of paint decoration. DETAILED DESCRIPTION

[0018] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution in the present invention is described clearly and completely. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] The present invention will be further described below in conjunction with the embodiments.

[0020] Embodiment 1: S100, Preparation of water-based acrylic emulsion: S101, Raw material preparation: Monomers: methyl methacrylate, butyl acrylate and hydroxyethyl acrylate, in a molar ratio of 3:2:1; Initiator: ammonium persulfate, the dosage is 0.5% of the total weight of monomers; Molecular weight regulator: dodecyl mercaptan, the amount is 0.2% of the total weight of the monomer; Water: The dosage is 1.5 times the total weight of the monomer; S102, polymerization reaction: adding monomer, initiator, molecular weight regulator and water into a reaction kettle, stirring evenly, heating to 70°C, starting the reaction, maintaining the temperature at 70-80°C during the reaction, and the reaction time is 4 hours; S103. After the reaction is completed, the mixture is cooled to room temperature to obtain an aqueous acrylic emulsion. The obtained aqueous acrylic emulsion has a glass transition temperature of 10° C., an average particle size of 0.1 μm, and a solid content of 40%.

[0021] S200, Preparation of waterborne polyurethane emulsion: S201, raw material preparation: polytetramethylene ether glycol (molecular weight 1000) and isophorone diisocyanate, molar ratio 1:2; S202, adding polytetramethylene ether glycol and isophorone diisocyanate into a reaction kettle, and reacting at 80° C. for 2 hours to obtain a prepolymer; S203, chain extension reaction: dimethylol propionic acid (in an amount of 5% by weight of the prepolymer) and ethylenediamine (in an amount of 3% by weight of the prepolymer) are added to the prepolymer, and a chain extension reaction is carried out at 50°C; S204, neutralization and emulsification: After the reaction is completed, triethylamine is added for neutralization, and the neutralization degree is 80%. Water is then added for emulsification to obtain an aqueous polyurethane emulsion. The aqueous polyurethane emulsion has an NCO content of 3% and a number average molecular weight of 5000.

[0022] S300, Surface treatment of titanium dioxide: S301, Raw material preparation: Titanium dioxide: rutile type, particle size 0.2μm, content 5 parts; Surface treatment agent: silane coupling agent (γ-aminopropyl triethoxysilane) and aluminate coupling agent (isopropyl tri(isostearoyl) titanate), the mass ratio is 1:1, and the amount of coupling agent is 2% of the weight of titanium dioxide; S302, treatment process: drying the titanium dioxide at 100° C. for 2 hours, adding a coupling agent, and mixing at a high-speed stirring of 1000 rpm for 30 minutes.

[0023] S400, coating treatment of red iron oxide: S401, Raw material preparation: Red iron oxide: content is 5 parts, particle size is 0.1μm; Coating material: silicone resin, the dosage is 5% of the weight of red iron oxide; Organic solvent: toluene; S402, treatment step: dispersing red iron oxide in toluene to a concentration of 20%, adding silicone resin, stirring and reacting at 60° C. for 2 hours at a stirring speed of 800 rpm; S403, after the reaction is completed, filter and dry to obtain coated iron oxide red.

[0024] S500, calcination treatment of kaolin: S501, raw material preparation: kaolin: particle size 1 μm, content 15 parts; S502, calcination process: calcine the kaolin at 800°C for 2 hours. The calcined kaolin has a whiteness of 90% and a Mohs hardness of 2.

[0025] S600, surface modification of heavy calcium carbonate: S601, Raw material preparation: Heavy calcium carbonate: particle size is 5μm, content is 15 parts; Modifier: stearic acid, the dosage is 1% of the weight of heavy calcium carbonate; S602, modification process: dry the heavy calcium carbonate at 100° C. for 1 hour, add stearic acid, and mix in a high-speed mixer at 1200 rpm for 20 minutes.

[0026] S700, Synthesis of Polycarboxylic Acid Sodium Salt Dispersant: S701, Raw material preparation: Monomers: acrylic acid, maleic anhydride and methyl methacrylate, in a molar ratio of 2:1:1; Initiator: sodium persulfate, the dosage is 0.3% of the total weight of monomers; Chain transfer agent: mercaptoethanol, the dosage is 0.1% of the total weight of the monomer; Water: The dosage is twice the total weight of the monomer; S702, synthesis reaction: adding monomer, initiator, chain transfer agent and water into a reaction kettle, reacting at 80° C. for 3 hours to obtain a polycarboxylate sodium salt dispersant with a molecular weight of 5,000.

[0027] Preparation of S800, Hydroxyethyl Cellulose: S801, Raw material preparation: Refined cotton; Alkali solution: concentration is 18%; The mass ratio of ethylene oxide to refined cotton is 2:1; S802, preparation process: Soak refined cotton in alkaline solution for 1 hour, then add ethylene oxide, react for 4 hours at a pressure of 0.2MPa and a temperature of 50°C. After the reaction, neutralize, wash and dry to obtain hydroxyethyl cellulose with a degree of substitution of 1.5.

[0028] S900. Preparation of a coating composition: 13.3 parts of the above-prepared aqueous acrylic emulsion, 6.7 parts of aqueous polyurethane emulsion, 5 parts of surface-treated titanium dioxide, 5 parts of coated red iron oxide, 15 parts of calcined kaolin, 15 parts of surface-modified heavy calcium carbonate, 2 parts of sodium polycarboxylate dispersant, 3 parts of hydroxyethyl cellulose, and 1 part of aqueous ammonia (concentration of 25%) are mixed uniformly to obtain an environmentally friendly coating composition for building interiors.

[0029] Embodiment 2: S100, Preparation of water-based acrylic emulsion: S101, Raw material preparation: Monomers: methyl methacrylate, butyl acrylate and hydroxyethyl acrylate, in a molar ratio of 3:2:1; Initiator: ammonium persulfate, the dosage is 0.8% of the total weight of monomers; Molecular weight regulator: dodecyl mercaptan, the amount used is 0.25% of the total weight of the monomer; Water: The dosage is 1.8 times the total weight of the monomer; S102, polymerization reaction: adding monomer, initiator, molecular weight regulator and water into a reaction kettle, stirring evenly, heating to 75°C, starting the reaction, maintaining the temperature at 70-80°C during the reaction, and the reaction time is 5 hours; S103. After the reaction is completed, the mixture is cooled to room temperature to obtain an aqueous acrylic emulsion. The obtained aqueous acrylic emulsion has a glass transition temperature of 15° C., an average particle size of 0.15 μm, and a solid content of 45%.

[0030] S200, Preparation of waterborne polyurethane emulsion: S201, raw material preparation: polytetramethylene ether glycol (molecular weight 1500) and isophorone diisocyanate, the molar ratio is 1:2; S202, adding polytetramethylene ether glycol and isophorone diisocyanate into a reaction kettle, and reacting at 85° C. for 2.5 hours to obtain a prepolymer; S203, chain extension reaction: add dimethylol propionic acid (in an amount of 8% by weight of the prepolymer) and ethylenediamine (in an amount of 4% by weight of the prepolymer) to the prepolymer, and carry out chain extension reaction at 55°C; S204, neutralization and emulsification: After the reaction is completed, triethylamine is added for neutralization, and the neutralization degree is 85%. Water is then added for emulsification to obtain an aqueous polyurethane emulsion. The aqueous polyurethane emulsion has an NCO content of 4% and a number average molecular weight of 8000.

[0031] S300, Surface treatment of titanium dioxide: S301, Raw material preparation: Titanium dioxide: rutile type, particle size 0.25μm, content 8 parts; Surface treatment agent: silane coupling agent (γ-aminopropyl triethoxysilane) and aluminate coupling agent (isopropyl tri(isostearoyl) titanate), the mass ratio is 1:1, and the amount of coupling agent is 2.5% of the weight of titanium dioxide; S302, treatment process: drying the titanium dioxide at 110° C. for 2.5 hours, adding a coupling agent, and mixing at a high-speed stirring of 1200 rpm for 45 minutes.

[0032] S400, coating treatment of red iron oxide: S401, Raw material preparation: Red iron oxide: content is 8 parts, particle size is 0.15μm; Coating material: silicone resin, the dosage is 8% of the weight of red iron oxide; Organic solvent: toluene; S402, treatment step: dispersing red iron oxide in toluene to a concentration of 25%, adding silicone resin, stirring and reacting at 65° C. for 2.5 hours at a stirring speed of 900 rpm; S403, after the reaction is completed, filter and dry to obtain coated iron oxide red.

[0033] S500, calcination treatment of kaolin: S501, raw material preparation: kaolin: particle size 3 μm, content 18 parts; S502, calcination process: calcine the kaolin at 850°C for 2.5 hours. The calcined kaolin has a whiteness of 93% and a Mohs hardness of 2.5.

[0034] S600, surface modification of heavy calcium carbonate: S601, Raw material preparation: Heavy calcium carbonate: particle size is 8μm, content is 18 parts; Modifier: stearic acid, the dosage is 1.5% of the weight of heavy calcium carbonate; S602, modification process: dry the heavy calcium carbonate at 105° C. for 1.5 hours, add stearic acid, and mix in a high-speed mixer at 1300 rpm for 25 minutes.

[0035] S700, Synthesis of Polycarboxylic Acid Sodium Salt Dispersant: S701, Raw material preparation: Monomers: acrylic acid, maleic anhydride and methyl methacrylate, in a molar ratio of 2:1:1; Initiator: sodium persulfate, the dosage is 0.4% of the total weight of monomers; Chain transfer agent: mercaptoethanol, the dosage is 0.15% of the total weight of the monomer; Water: The dosage is 2.5 times the total weight of the monomer; S702, synthesis reaction: adding monomer, initiator, chain transfer agent and water into a reaction kettle, reacting at 85° C. for 3.5 hours to obtain a polycarboxylate sodium salt dispersant with a molecular weight of 6500.

[0036] Preparation of S800, Hydroxyethyl Cellulose: S801, Raw material preparation: Refined cotton; Alkali solution: concentration is 19%; The mass ratio of ethylene oxide to refined cotton is 2:1; S802, preparation process: Soak refined cotton in alkaline solution for 1.5 hours, then add ethylene oxide, react for 4.5 hours at a pressure of 0.25 MPa and a temperature of 55°C. After the reaction, neutralize, wash and dry to obtain hydroxyethyl cellulose with a degree of substitution of 1.8.

[0037] S900. Preparation of a coating composition: 16 parts of the above-prepared aqueous acrylic emulsion, 8 parts of aqueous polyurethane emulsion, 8 parts of surface-treated titanium dioxide, 8 parts of coated red iron oxide, 18 parts of calcined kaolin, 18 parts of surface-modified heavy calcium carbonate, 3 parts of sodium polycarboxylate dispersant, 4 parts of hydroxyethyl cellulose, and 2 parts of aqueous ammonia (concentration of 26%) are mixed uniformly to obtain an environmentally friendly coating composition for building interiors.

[0038] Embodiment three: S100, Preparation of water-based acrylic emulsion: S101, Raw material preparation: Monomers: methyl methacrylate, butyl acrylate and hydroxyethyl acrylate, in a molar ratio of 3:2:1; Initiator: ammonium persulfate, the dosage is 1% of the total weight of monomers; Molecular weight regulator: dodecyl mercaptan, the dosage is 0.3% of the total weight of the monomer; Water: The dosage is twice the total weight of the monomer; S102, polymerization reaction: adding monomer, initiator, molecular weight regulator and water into a reaction kettle, stirring evenly, heating to 80°C, starting the reaction, maintaining the temperature at 70-80°C during the reaction, and the reaction time is 6 hours; After the reaction was completed, the mixture was cooled to room temperature to obtain an aqueous acrylic emulsion. The obtained aqueous acrylic emulsion had a glass transition temperature of 20° C., an average particle size of 0.2 μm, and a solid content of 50%.

[0039] S200, Preparation of waterborne polyurethane emulsion: S201, raw material preparation: polytetramethylene ether glycol (molecular weight 2000) and isophorone diisocyanate, molar ratio 1:2; S202, adding polytetramethylene ether glycol and isophorone diisocyanate into a reaction kettle, and reacting at 90° C. for 3 hours to obtain a prepolymer; S203, chain extension reaction: dimethylol propionic acid (in an amount of 10% by weight of the prepolymer) and ethylenediamine (in an amount of 5% by weight of the prepolymer) are added to the prepolymer, and a chain extension reaction is carried out at 60°C; S204, neutralization and emulsification: after the reaction is completed, triethylamine is added for neutralization, the neutralization degree is 90%, and then water is added for emulsification to obtain a waterborne polyurethane emulsion; The NCO content of the aqueous polyurethane emulsion is 5%, and the number average molecular weight is 10,000.

[0040] S300, Surface treatment of titanium dioxide: S301, Raw material preparation: Titanium dioxide: rutile type, particle size 0.3μm, content 10 parts; Surface treatment agent: silane coupling agent (γ-aminopropyl triethoxysilane) and aluminate coupling agent (isopropyl tri(isostearoyl) titanate), the mass ratio is 1:1, and the amount of coupling agent is 3% of the weight of titanium dioxide; S302, treatment process: drying the titanium dioxide at 120° C. for 3 hours, adding a coupling agent, and mixing at a high-speed stirring of 1500 rpm for 60 minutes.

[0041] S400, coating treatment of red iron oxide: S401, Raw material preparation: Red iron oxide: content is 10 parts, particle size is 0.2μm; Coating material: silicone resin, the dosage is 10% of the weight of red iron oxide; Organic solvent: toluene; S402, treatment step: dispersing red iron oxide in toluene to a concentration of 30%, adding silicone resin, stirring and reacting at 70° C. for 3 hours at a stirring speed of 1000 rpm; S403, after the reaction is completed, filter and dry to obtain coated iron oxide red.

[0042] S500, calcination treatment of kaolin: S501, raw material preparation: kaolin: particle size 5 μm, content 20 parts; S502, calcination process: calcine the kaolin at 900°C for 3 hours. The calcined kaolin has a whiteness of 95% and a Mohs hardness of 3.

[0043] S600, surface modification of heavy calcium carbonate: S601, Raw material preparation: Heavy calcium carbonate: particle size is 10μm, content is 20 parts; Modifier: stearic acid, the dosage is 2% of the weight of heavy calcium carbonate; S602, modification process: dry the heavy calcium carbonate at 110° C. for 2 hours, add stearic acid, and mix in a high-speed mixer at 1500 rpm for 30 minutes.

[0044] S700, Synthesis of Polycarboxylic Acid Sodium Salt Dispersant: S701, Raw material preparation: Monomers: acrylic acid, maleic anhydride and methyl methacrylate, in a molar ratio of 2:1:1; Initiator: sodium persulfate, the dosage is 0.5% of the total weight of monomers; Chain transfer agent: mercaptoethanol, the dosage is 0.2% of the total weight of the monomer; Water: The dosage is 3 times the total weight of the monomer; S702, synthesis reaction: adding monomer, initiator, chain transfer agent and water into a reaction kettle, reacting at 90° C. for 4 hours to obtain a polycarboxylate sodium salt dispersant with a molecular weight of 8,000.

[0045] Preparation of S800, Hydroxyethyl Cellulose: S801, Raw material preparation: Refined cotton; Alkali solution: concentration is 20%; The mass ratio of ethylene oxide to refined cotton is 2:1; S802, preparation process: Soak refined cotton in alkaline solution for 2 hours, then add ethylene oxide, and react for 5 hours under the conditions of pressure of 0.3MPa and temperature of 60°C. After the reaction, neutralize, wash and dry to obtain hydroxyethyl cellulose with a degree of substitution of 2.0.

[0046] S900. Preparation of a coating composition: uniformly mix 20 parts of the above-prepared aqueous acrylic emulsion, 10 parts of aqueous polyurethane emulsion, 10 parts of surface-treated titanium dioxide, 10 parts of coated red iron oxide, 20 parts of calcined kaolin, 20 parts of surface-modified heavy calcium carbonate, 5 parts of sodium polycarboxylate dispersant, 6 parts of hydroxyethyl cellulose, and 3 parts of aqueous ammonia (concentration of 28%) to obtain an environmentally friendly coating composition for building interiors.

[0047] The examples are compared, and the comparison results are as follows: Table 1: Comparison of preparation conditions of water-based acrylic emulsion

[0048] In Table 1: Initiator dosage: In Example 1, the initiator dosage is 0.5% of the total weight of the monomers, in Example 2 it is 0.8%, and in Example 3 it is 1%. As the initiator dosage increases, the reaction activity increases, which helps the monomers to polymerize more fully, thereby affecting the performance of the emulsion.

[0049] Amount of molecular weight regulator: From Example 1 to Example 3, the amount of molecular weight regulator is gradually increased from 0.2% to 0.3% of the total weight of the monomer. The change in the amount can adjust the molecular weight distribution of the polymer and affect the viscosity and film-forming properties of the emulsion.

[0050] Water dosage: The water dosage in the three examples is 1.5 times, 1.8 times and 2 times the total weight of the monomers, respectively. The increase in water dosage will change the concentration of the reaction system, affecting the polymerization reaction rate and the stability of the emulsion.

[0051] Reaction temperature and time: The reaction temperatures are all in the range of 70-80°C, but the starting temperatures are different. Example 1 starts from 70°C, Example 2 starts from 75°C, and Example 3 starts from 80°C. The reaction time is gradually extended from 4 hours to 6 hours. The adjustment of the reaction temperature and time will affect the degree of polymerization and the properties of the emulsion, such as glass transition temperature, average particle size and solid content.

[0052] Table 2: Comparison of water-based acrylic emulsion performance

[0053] In Table 2: Glass transition temperature: 10°C, 15°C and 20°C respectively. The increase in glass transition temperature indicates that the rigidity of the emulsion polymer increases and the heat resistance may improve, but the flexibility may decrease, affecting the application scope and performance of the coating.

[0054] Average particle size: increases from 0.1μm to 0.2μm. The change in particle size will affect the stability, glossiness and hiding power of the emulsion. The emulsion with smaller particle size has better stability and glossiness, but the hiding power is relatively weaker.

[0055] Solid content: increased from 40% to 50%. The increase in solid content means more effective ingredients in the emulsion, which can reduce the use of solvents in the coating formulation, reduce VOC emissions, and improve the drying speed and film performance of the coating.

[0056] Table 3: Comparison of preparation conditions of waterborne polyurethane emulsion

[0057] In Table 3: Raw material molar ratio and molecular weight: The molar ratio of polytetramethylene ether glycol to isophorone diisocyanate is always 1:2, but the molecular weight of polytetramethylene ether glycol increases from 1000 to 2000. The change in raw materials will affect the structure and properties of the prepolymer, and then affect the characteristics of the final emulsion.

[0058] Prepolymer reaction conditions: The reaction temperature increased from 80°C to 90°C, and the time was extended from 2 hours to 3 hours. The change of prepolymer reaction conditions will affect the reaction degree and product structure, and affect the subsequent chain extension reaction and emulsion performance.

[0059] Chain extender dosage and neutralization degree: The dosage of dimethylolpropionic acid and ethylenediamine gradually increases, and the neutralization degree increases from 80% to 90%. Changes in the chain extender dosage and neutralization degree will adjust the properties of the emulsion, such as molecular weight, crosslinking degree and stability.

[0060] Table 4: Comparison of waterborne polyurethane emulsion performance

[0061] In Table 4: NCO content and number average molecular weight: When the NCO content increases from 3% to 5%, the number average molecular weight increases from 5000 to 10000. The changes in NCO content and molecular weight will significantly affect the flexibility, wear resistance, tensile strength and elongation at break of the emulsion, thus changing its application characteristics in the coating.

[0062] Table 5: Titanium dioxide related comparison

[0063] In Table 5: Particle size and content: The particle size increases from 0.2μm to 0.3μm, and the content increases from 5 parts to 10 parts. The changes in particle size and content will affect the hiding power, whiteness and dispersibility of the coating. Larger particle size and higher content improve hiding power, but increase the difficulty of dispersion.

[0064] Surface treatment conditions: The amount of surface treatment agent increased from 2% to 3% of the weight of titanium dioxide, the drying temperature increased from 100°C to 120°C, the stirring speed increased from 1000rpm to 1500rpm, and the treatment time extended from 30 minutes to 60 minutes. The strengthening of surface treatment conditions helps to improve the dispersibility of titanium dioxide in the coating, the binding force with the film-forming material and the weather resistance.

[0065] Table 6: Red Iron Oxide Comparison

[0066] In Table 6: Particle size and content: The particle size increases from 0.1μm to 0.2μm, and the content increases from 5 parts to 10 parts. Changes in particle size and content will affect the color intensity, hiding power and dispersibility of the coating. Larger particle size and higher content make the color brighter, but attention should be paid to dispersibility.

[0067] Coating treatment conditions: the amount of coating material increased from 5% to 10% of the weight of red iron oxide, the dispersion concentration increased from 20% to 30%, the reaction temperature increased from 60°C to 70°C, the stirring speed increased from 800rpm to 1000rpm, and the reaction time extended from 2 hours to 3 hours. The optimization of coating treatment conditions can enhance the acid and alkali resistance, chemical stability and color retention of red iron oxide.

[0068] Table 7: Kaolin related comparison

[0069] In Table 7: Particle size and content: The particle size increases from 1μm to 5μm, and the content increases from 15 parts to 20 parts. The changes in particle size and content will affect the hardness, wear resistance, filling and leveling of the coating. Larger particle size and higher content improve hardness and filling, but the leveling is affected to a certain extent.

[0070] Calcination conditions and properties: The calcination temperature increased from 800℃ to 900℃, and the time was extended from 2 hours to 3 hours. After calcination, the whiteness increased from 90% to 95%, and the Mohs hardness increased from 2 to 3. The change in calcination conditions made the kaolin crystal structure more regular and the flaky structure more obvious, which improved the hardness, wear resistance and whiteness of the coating without affecting the leveling property.

[0071] Table 8: Comparison of heavy calcium carbonate

[0072] In Table 8: Particle size and content: The particle size increases from 5μm to 10μm, and the content increases from 15 parts to 20 parts. The changes in particle size and content will affect the filling performance, oil absorption value and dispersibility of the coating. Larger particle size and higher content improve filling performance, but oil absorption value and dispersibility need attention.

[0073] Modification conditions and effects: The amount of modifier stearic acid increased from 1% to 2% of the weight of heavy calcium carbonate, the drying temperature increased from 100°C to 110°C, the stirring speed increased from 1200rpm to 1500rpm, and the mixing time extended from 20 minutes to 30 minutes. Surface modification significantly improved the dispersibility of heavy calcium carbonate in the coating and its compatibility with film-forming substances, reduced the oil absorption value, and reduced storage precipitation.

[0074] Table 9: Comparison of sodium polycarboxylate dispersants

[0075] In Table 9: Synthesis conditions: The monomer molar ratio was always 2:1:1, but the amount of initiator increased from 0.3% to 0.5% of the total monomer weight, the amount of chain transfer agent increased from 0.1% to 0.2%, the amount of water increased from 2 times to 3 times the total monomer weight, the reaction temperature increased from 80°C to 90°C, and the time was extended from 3 hours to 4 hours. The changes in the synthesis conditions affected the molecular weight and performance of the dispersant. The optimized conditions can improve its dispersion performance and stability.

[0076] Molecular weight: The molecular weight increases from 5000 to 8000. The increase in molecular weight helps to enhance the dispersing effect of the dispersant on pigments and fillers, so that the coating composition maintains a better dispersed state during storage and prevents agglomeration.

[0077] Table 10: Comparison of hydroxyethyl cellulose

[0078] In Table 10: Preparation conditions: the concentration of alkali solution increased from 18% to 20%, the soaking time extended from 1 hour to 2 hours, the reaction pressure increased from 0.2MPa to 0.3MPa, the temperature increased from 50℃ to 60℃, and the time extended from 4 hours to 5 hours. The changes in preparation conditions will affect the degree of substitution and performance of hydroxyethyl cellulose.

[0079] Degree of substitution and performance: The degree of substitution is increased from 1.5 to 2.0. The higher degree of substitution enables hydroxyethyl cellulose to more effectively adjust the rheological properties in the coating, improve the construction performance, make the coating film more uniform and smooth, and reduce sagging.

[0080] Table 11: Comparison of coating composition ratios

[0081] In Table 11: Changes in the amount of each component: The amount of water-based acrylic emulsion and water-based polyurethane emulsion gradually increases in the three embodiments, and the amount of pigment (titanium dioxide and red iron oxide), filler (kaolin and heavy calcium carbonate), dispersant, thickener and pH adjuster (ammonia water) also increases to varying degrees. The adjustment of the amount of each component will comprehensively affect the performance of the coating, such as film-forming properties, hiding power, hardness, rheological properties, etc., to meet different usage needs and performance requirements.

[0082] Comparative Example 1: It is an existing common coating composition (similar in composition to the coating composition of the present invention, but does not adopt the specific film-forming substance combination, pigment processing method, filler processing method, etc. of the present invention).

[0083] The coating compositions prepared in Examples 1 to 3 of the present invention were tested for performance comparison, and the specific test items and results are as follows: Water resistance test: Test method: Test in accordance with GB / T1733-1993 "Determination of water resistance of paint films". Immerse the prepared paint sample (size: 100mm×50mm×1mm) in distilled water at (23±2)℃ for 48h, observe the changes on the sample surface, and record the bubbling, peeling, rusting and other phenomena of the paint film.

[0084] Table 12: Water resistance test results

[0085] Weathering test: Test method: Use QUV aging test chamber to carry out artificial accelerated aging test, according to GB / T1865-2009 "Artificial weathering and artificial radiation exposure to filtered xenon arc radiation for paints and varnishes", set the light intensity to 0.68W / m²・nm (340nm), the blackboard temperature to (65±3)℃, the relative humidity to (50±5)%, the water spraying cycle to 18min / 102min (water spraying during light), and the test time to 1000h. After the test, observe the surface of the sample for powdering, cracking, discoloration, etc.

[0086] Table 13: Weathering test results

[0087] Flexibility test: Test method: Test in accordance with GB / T1731-1993 "Determination of paint film flexibility". Place the paint sample at (23±2)℃ and relative humidity (50±5)% for 24 hours, then test it on a flexibility tester, observe the cracking of the paint film after the sample is bent, and record the minimum bending diameter.

[0088] Table 14: Flexibility test results

[0089] Abrasion resistance test: Test method: Taber abrasion tester is used for testing in accordance with GB / T1768-2006 "Determination of abrasion resistance of paints and varnishes - Rotating rubber wheel method". The loading weight is 1000g and the rotation speed is 72r / min. After each sample is tested for 1000 revolutions, the weight loss of the sample is measured. The smaller the weight loss, the better the wear resistance.

[0090] Table 15: Wear resistance test results

[0091] Dispersion test: Test method: Use a laser particle size analyzer to analyze the particle size distribution of pigments and fillers in the coating composition, observe the agglomeration of particles, and calculate the dispersion index (DI). The smaller the DI value, the better the dispersion.

[0092] Table 16: Dispersion test results

[0093] Hiding power test: Test method: Test in accordance with GB / T1726-1979 "Determination of hiding power of paints". Apply the paint evenly on the black and white grid glass plate to make the paint film thickness reach the specified requirements. Then, under scattered light conditions, use a reflectivity meter to measure the reflectivity on the black and white grid and calculate the hiding power. The smaller the hiding power, the stronger the hiding ability of the paint.

[0094] Table 17: Hiding power test results

[0095] Color retention test: Test method: Soak the paint samples in an acidic and alkaline environment (acidic solution with pH=2 and alkaline solution with pH=10) for 72 hours respectively, take them out and dry them at room temperature for 24 hours, then use a colorimeter to measure the color change of the samples before and after soaking, and calculate the color difference value (ΔE). The smaller the ΔE value, the better the color retention.

[0096] Table 18: Color retention test results

[0097] Analysis and description: It can be seen from the performance comparison test results of the above comparative examples and embodiments that the environmentally friendly coating composition of the present invention is significantly superior to the existing ordinary coating compositions in terms of water resistance, weather resistance, flexibility, abrasion resistance, dispersibility, hiding power and color retention. This is because the present invention adopts a water-based acrylic emulsion and a water-based polyurethane emulsion mixed in a specific proportion as film-forming substances. The synergistic effect of the two makes the paint film have good density and adhesion, thereby improving the overall performance of the coating.

[0098] Surface treatment of titanium dioxide enhances its dispersibility in the coating and its binding force with film-forming substances, thereby improving the hiding power and coating performance; coating treatment of red iron oxide effectively improves its acid and alkali resistance and chemical stability, ensuring long-term color brightness; calcination of kaolin and surface modification of heavy calcium carbonate improve the performance of fillers in the coating, achieving a better balance in hardness, wear resistance, filling and leveling properties; sodium polycarboxylate dispersants and hydroxyethyl cellulose prepared by a specific synthesis method improve the dispersion stability and rheological properties of the coating, respectively, ensuring the good performance of the coating during construction.

[0099] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. An environmentally friendly coating composition for building interiors, characterized in that: The composition comprises the following basic components in parts by weight: 20-30 parts of a film-forming substance, 10-20 parts of a pigment, 30-40 parts of a filler, 2-5 parts of a dispersant, 3-6 parts of a thickener, and 1-3 parts of a pH regulator; The film-forming substance is formed by mixing an aqueous acrylic emulsion and an aqueous polyurethane emulsion in a ratio of 2:1, the aqueous acrylic emulsion has a glass transition temperature of 10-20°C, an average particle size of 0.1-0.2 μm, and a solid content of not less than 40%, and the aqueous polyurethane emulsion has an NCO content of 3-5% and a number average molecular weight of 5000-10000; The pigments are titanium dioxide and red iron oxide. The titanium dioxide is rutile, with a particle size of 0.2-0.3 μm and a content of 5-10 parts. The content of red iron oxide is 5-10 parts and a particle size of 0.1-0.2 μm. The filler is a mixture of kaolin and heavy calcium carbonate, the particle size of kaolin is 1-5 μm, the content is 15-20 parts, the particle size of heavy calcium carbonate is 5-10 μm, the content is 15-20 parts; The dispersant is a polycarboxylate sodium salt dispersant, and its molecular weight is between 5000-8000; The thickener is hydroxyethyl cellulose, and its degree of substitution is 1.5-2.0; The pH regulator is ammonia water with a concentration of 25%-28%.

2. The environmentally friendly coating composition for building interiors according to claim 1, characterized in that: The aqueous acrylic emulsion is prepared by free radical polymerization. In the polymerization reaction, the monomers include methyl methacrylate, butyl acrylate and hydroxyethyl acrylate in a molar ratio of 3:2:1, the initiator is ammonium persulfate in an amount of 0.5-1% of the total weight of the monomers, the reaction temperature is controlled at 70-80°C, and the reaction time is 4-6 hours; During the polymerization process, dodecyl mercaptan, a molecular weight regulator, is added in an amount of 0.2-0.3% of the total weight of the monomers. In the reaction system, the amount of water is 1.5-2 times the total weight of the monomers.

3. The environmentally friendly coating composition for building interiors according to claim 1, characterized in that: The aqueous polyurethane emulsion is synthesized by a prepolymer method, and the specific steps are: Step 1, using polytetramethylene ether glycol and isophorone diisocyanate as raw materials, reacting at 80-90° C. for 2-3 hours to obtain a prepolymer, wherein the molecular weight of the polytetramethylene ether glycol is 1000-2000, and the molar ratio of isophorone diisocyanate to the polytetramethylene ether glycol is 2:1; Step 2, the prepolymer is subjected to a chain extension reaction with dimethylolpropionic acid and ethylenediamine at 50-60° C., wherein the amount of dimethylolpropionic acid is 5-10% by weight of the prepolymer, and the amount of ethylenediamine is 3-5% by weight of the prepolymer; Step 3: After the reaction is completed, triethylamine is added for neutralization with a neutralization degree of 80-90%, and then water is added for emulsification to obtain a waterborne polyurethane emulsion.

4. The environmentally friendly coating composition for building interiors according to claim 1, characterized in that: The titanium dioxide is surface treated before use. The surface treatment agent is a mixture of a silane coupling agent and an aluminate coupling agent. The silane coupling agent is γ-aminopropyl triethoxysilane and the aluminate coupling agent is isopropyl tri(isostearoyl) titanate. The mass ratio of the two is 1:

1. The amount of the surface treatment agent is 2-3% of the weight of the titanium dioxide. The treatment process is as follows: drying titanium dioxide at 100-120° C. for 2-3 hours, adding a coupling agent, and mixing for 30-60 minutes under high-speed stirring at a stirring speed of 1000-1500 rpm.

5. The environmentally friendly coating composition for building interiors according to claim 1, characterized in that: The red iron oxide is coated, and the coating material is an organic silicone resin, and the amount thereof is 5-10% of the weight of the red iron oxide; Specific processing steps: Step 1: Disperse red iron oxide in an organic solvent, wherein the organic solvent is toluene, and the concentration of red iron oxide is 20-30%; Step 2: Add silicone resin, stir and react at 60-70°C for 2-3 hours at a stirring speed of 800-1000 rpm; Step 3: After the reaction is completed, filter and dry to obtain coated iron oxide red.

6. The environmentally friendly coating composition for building interiors according to claim 1, characterized in that: The kaolin is calcined at a temperature of 800-900° C. and a calcination time of 2-3 hours. The calcined kaolin has a whiteness of 90-95% and a Mohs hardness of 2-3.

7. The environmentally friendly coating composition for building interiors according to claim 1, characterized in that: The heavy calcium carbonate is surface-modified, and the modifier is stearic acid, and the amount used is 1-2% of the weight of the heavy calcium carbonate; The modification process is as follows: drying the heavy calcium carbonate at 100-110° C. for 1-2 hours, adding stearic acid, and mixing in a high-speed mixer for 20-30 minutes at a mixing speed of 1200-1500 rpm.

8. The environmentally friendly coating composition for building interiors according to claim 1, characterized in that: The specific steps of the synthesis method of the polycarboxylate sodium salt dispersant are: Step 1: using acrylic acid, maleic anhydride and methyl methacrylate as monomers in a molar ratio of 2:1:1; Step 2: The initiator is sodium persulfate, and the amount used is 0.3-0.5% of the total weight of the monomer; Step 3: Add chain transfer agent mercaptoethanol to the reaction system in an amount of 0.1-0.2% of the total weight of the monomers. The reaction is carried out in an aqueous solution, the amount of water used is 2-3 times the total weight of the monomers, the reaction temperature is 80-90°C, and the reaction time is 3-4 hours.

9. The environmentally friendly coating composition for building interiors according to claim 1, characterized in that: The preparation process of the hydroxyethyl cellulose is as follows: using refined cotton as a raw material, soaking it in an alkali solution for 1-2 hours, the alkali solution concentration is 18-20%, adding ethylene oxide, the mass ratio of ethylene oxide to refined cotton is 2:1, reacting under the conditions of a pressure of 0.2-0.3MPa and a temperature of 50-60°C, the reaction time is 4-5 hours, and after the reaction is completed, neutralizing, washing, and drying to obtain the hydroxyethyl cellulose.

Citation Information

Patent Citations

  • Polycarboxylate dispersant and its preparation method

    CN103951798A

  • Preparation method of highly anti-sagging type acrylic coating

    CN108219618A

  • Environment-friendly high-performance water-based plastic industrial coating and preparation method thereof

    CN109627871A

  • Preparation method and application of waterborne polyurethane transfer glue emulsion

    CN109762128A

  • Water-based single-component high-fullness roller painting white primer as well as preparation method and application thereof

    CN114752267A